English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

f-g(x)=(x+2)-(3x^2-5) So
f-g(x)=x+7-3x^2

2006-11-05 13:45:29 · answer #1 · answered by fritters1018 1 · 0 0

f(x) = x + 2
g(x) = 3x^2 - 5

(f - g)(x) = (x + 2) - (3x^2 - 5) = x + 2 - 3x^2 + 5 = -3x^2 + x + 7

2006-11-05 23:37:30 · answer #2 · answered by Sherman81 6 · 0 0

(f-g)(x)=(x+2)-(3x^2-5)=x+2-3x^2+5=-3x^2+x+7

2006-11-05 21:45:52 · answer #3 · answered by Adonis_D 2 · 0 0

I have never seen this : (f-g)(x) , I know only f(x) - g(x) or g(x) - f(x)

2006-11-05 21:46:02 · answer #4 · answered by James Chan 4 · 0 0

fedest.com, questions and answers